The Role of Arabic Literature in Promoting Spiritual Values: A Model of Jalaluddin Rumi - Al-Barzanjy, Dr. Muhammad Latif Ahmad Al-Barzanjy (Sulaimani Journal for Humanities, 2026)
This research aims to explore the role of Arabic literature in promoting spiritual values, taking Jalal al-Din Rumi as a model for studying Sufi literature and its influence. The research addresses three main axes: The theoretical background of Sufi literature, Jalaluddin Rumi’s career as a Sufi poet and spiritual thinker, And an analysis of the spiritual values ​​​​in his works, such as divine love, trust, and tolerance. The research shows how Rumi's works were able to influence generations through global spiritual visions that transcended cultural boundaries. The research also discusses how to use literature as a means to deepen spirituality and achieve psychological and spiritual balance, highlighting the pivotal role of Sufism in enriching Arab and international literature.
Keywords: Sufi literature; spiritual values; Jalal adDin Rumi